HIV testing in re-education through labour camps in Guangxi Autonomous Region, China (a cross-sectional survey) - Lorraine Yap; Joanne Reekie; Wei Liu; Yi Chen; Zunyou Wu; Jianghong Li; Lei Zhang; Handan Wand; Basil Donovan; Tony Butler (Sexually Transmitted Infections, 2015)
[Objective:] HIV testing is mandatory in re-education-through-labour camps (laojiaosuo) in China yet no studies have reported on the process. [Methods:] The survey response rate was 100% although 29 detainees were excluded because they were under 18 years of age. A cross-sectional face-to-face survey was conducted in three labour camps in Guangxi, located in the south-western region of China. [Results:] Of the 755 detainees surveyed, 725 (96%) reported having a blood test in the labour camps of whom 493 (68%) thought this included an HIV test. 61 detainees self-reported they were HIV infected, their status confirmed by medical records, if available. Of these, 53 (87%) recalled receiving post-test HIV education, and 15 (25%) were currently receiving HIV antiretroviral therapy. Pretest education on HIV was provided to 233/725 (32%) detainees. The study further reports on detainees' reactions and feelings towards non-disclosure and disclosure of their HIV test results in the labour camps. [Conclusions:] Mandatory testing is almost universal in the labour camps although a proportion of detainees were unaware that this included an HIV test. HIV test results should be disclosed to all labour camp detainees to reduce their distress of not knowing and prevent misconceptions about their HIV status. Labour camps provide another opportunity to implement universal treatment (`Test and Treat') to prevent the spread of HIV.
Keywords: 300